Dual-energy CT with virtual monochromatic images and metal artifact reduction software for reducing metallic dental artifacts. (November 2017) - Cha, Jihoon; Kim, Hyung-Jin; Kim, Sung Tae; Kim, Yi Kyung; Kim, Ha Youn; Park, Gyeong Min
Background: Metallic dental prostheses may degrade image quality on head and neck computed tomography (CT). However, there is little information available on the use of dual-energy CT (DECT) and metal artifact reduction software (MARS) in the head and neck regions to reduce metallic dental artifacts. Purpose: To assess the usefulness of DECT with virtual monochromatic imaging and MARS to reduce metallic dental artifacts. Material and Methods: DECT was performed using fast kilovoltage (kV)-switching between 80-kV and 140-kV in 20 patients with metallic dental prostheses. CT data were reconstructed with and without MARS, and with synthesized monochromatic energy in the range of 40–140-kiloelectron volt (keV). For quantitative analysis, the artifact index of the tongue, buccal, and parotid areas was calculated for each scan. For qualitative analysis, two radiologists evaluated 70-keV and 100-keV images with and without MARS for tongue, buccal, parotid areas, and metallic denture. The locations and characteristics of the MARS-related artifacts, if any, were also recorded. Results: DECT with MARS markedly reduced metallic dental artifacts and improved image quality in the buccal area ( P  < 0.001) and the tongue ( P  < 0.001), but not in the parotid area. The margin and internal architecture of the metallic dentures were more clearly delineated with MARS ( P  < 0.001) and in the higher-energy images than in the lower-energy images ( P  = 0.042). MARS-related artifacts most commonly occurred in the deep center of the neck. Conclusion: DECT with MARS can reduce metallic dental artifacts and improve delineation of the metallic prosthesis and periprosthetic region.